Ex Vivo Drug Susceptibility of Ferroquine against Chloroquine-Resistant Isolates of Plasmodium falciparum and P. vivax - Marfurt, Jutta (American Society for Microbiology, 2011)
Ferroquine (FQ; SSR97193), a ferrocene-containing 4-aminoquinoline derivate, has potent in vitro efficacy against chloroquine (CQ)-resistant Plasmodium falciparum and CQ-sensitive P. vivax. In the current study, ex vivo FQ activity was tested in multidrug-resistant P. falciparum and P. vivax field isolates using a schizont maturation assay. Although FQ showed excellent activity against CQ-sensitive and -resistant P. falciparum and P. vivax (median 50% inhibitory concentrations [IC(50)s], 9.6 nM and 18.8 nM, respectively), there was significant cross-susceptibility with the quinoline-based drugs chloroquine, amodiaquine, and piperaquine (for P. falciparum, r = 0.546 to 0.700, P < 0.001; for P. vivax, r = 0.677 to 0.821, P < 0.001). The observed ex vivo cross-susceptibility is likely to reflect similar mechanisms of drug uptake/efflux and modes of drug action of this drug class. However, the potent activity of FQ against resistant isolates of both P. falciparum and P. vivax highlights a promising role for FQ as a lead antimalarial against CQ-resistant Plasmodium and a useful partner drug for artemisinin-based combination therapy.